Parathyroid Adenoma With Respiratory-Like Epithelium: Case Report of a Potential Mimic With Unknown Etiology - Juhlin, C. Christofer; Zedenius, Jan (Frontiers in Endocrinology, 2021)
Parathyroid adenoma is a tumor composed of increased parenchymal tissue, often built-up by chief cells, transitional cells or oncocytic cells arranged in acinar or solid formations. Occasionally, rare histological patterns are reported, including cystic or trabecular arrangements. We present a 47 year-old male patient with primary hyperparathyroidism who underwent focused parathyroidectomy for a right inferior adenoma. Surgery was uneventful, but histologically, normal parathyroid tissue adjacent to a tumorous structure displaying a cystic growth pattern was detected. The cells lining the cyst walls appeared cylindrical and pseudo-stratified, vaguely reminiscent of a respiratory type of epithelium usually associated to branchial cleft cysts or thyroglossal cyst remnants, albeit with a tumorous appearance. The respiratory-like epithelium stained positive for parathyroid markers PTH and GATA3, thereby confirming them as parathyroid-derived. The patient was cured from surgery as he displayed normal calcium and PTH levels postoperatively, and is currently alive and well without signs of relapse 4 years after surgery. This is to our knowledge the first report of a parathyroid tumor displaying a respiratory-like epithelium. Experimentally, canine parathyroid glands can develop ciliated respiratory epithelium in response to inhalation of ozone. Our patient is a construction worker with a hypothetically increased risk of continuous ozone exposure. Although this association remains purely speculative, future investigations of this tumor phenotype could perhaps yield novel insights regarding the frequency of this histological variant, potential clinical associations, and clues regarding influencing factors.